Coastal Land Dynamics in South-Eastern Bangladesh: Interplay of Climate Forcing and Mangrove Ecosystems - Barua, Prabal; Nargis, Nahida (Journal of Hydrological Ecology and Water Security, 2025)
Coastal land erosion and accretion (EA) are highly dynamic processes influenced by local climatic variability, often resulting in land loss and population displacement in Bangladesh. This study examines the linkages between climatic variables and coastal land transformations by analyzing 33 years of daily precipitation and temperature data from multiple meteorological stations. Following a moving average smoothing process, three statistical approaches—Spearman’s rank, Pearson’s, and Kendall’s tau correlations—were applied to identify robust associations. Results demonstrate a strong rainfall–temperature relationship (0.78–0.85), exhibiting consistent spatial patterns with minor regional variations. Annual correlation analyses were calibrated against observed erosion and accretion rates, indicating that Kutubdia loses approximately 0.29 km² of land annually, while Sandwip, Teknaf, and Sitakund gain 0.59, 7.6, and 7.3 km² per year, respectively. Mangrove ecosystems substantially enhance shoreline stability, with trunk densities of 30–40 per m² and inland coverage extending about 200 m from creek margins. Mangrove-dominated zones such as Cox’s Bazar show net land gains of around 0.6 km² annually. Overall, spatial heterogeneity in southeastern coastal dynamics reflects both erosional vulnerability and accretional resilience. The study proposes an integrated, scalable framework that couples climatic and ecological indicators for sustainable coastal land management and climate resilience planning.